Implementation of PBL Learning Model Assisted As Media Diorama to Improve Thematic Learning Achievement of Class III Students at SDN Alastuwo 1 Magetan - Jaya Dwi Partika; Joko Widianto; Suwarni Suwarni (STKIP Taman Siswa Bima, 2023)
The low learning achievement of the thematic content of Indonesian and PPKN of class III students of Alastuwo 1 Elementary School was the background for conducting this research. Based on the results of observations and test scores for the thematic subjects of PPKN and Indonesian, it showed low student learning outcomes. This research is a classroom action research carried out with the aim of increasing the thematic learning achievement of class III students at SDN Alastuwo 1 using the PBL learning model assisted by Diorama media. This research will be conducted in 2 cycles. Each cycle in this Action consists of four stages, namely planning, implementing, observing, and reflecting. The subjects in this study were class III students at SDN Alastuwo 1, totaling 18 children. The data collection technique in this study used the multiple choice test method. Data analysis in this study uses qualitative and quantitative. The results showed that the average thematic learning achievement in cycle I was 69.87% and in cycle II was 75.75%. Based on the results of the study, it can be concluded that there is an increase in thematic learning achievement of class III students at SDN Alastuwo 1 Magetan after learning by applying the PBL model assisted by Diorama media.